Changing spatiotemporal dependence of the precipitation-temperature during Indian Summer Monsoon using observational and CMIP6 model simulations - Anjali Chaudhary; Ravi Kumar Guntu; Sachidanand Sharma; Ankit Agarwal (Journal of Hydrology: Regional Studies, 2025)
Study region: Indian mainland Study focus: Quantifying precipitation-temperature (P-T) dependence is essential for understanding emerging patterns of compound extremes, especially in climate-vulnerable countries like India. The present study investigates the spatiotemporal variability of P-T dependence during the Indian Summer Monsoon using observational data and CMIP6 model simulations. We evaluated the performance of CMIP6 simulations and projected changes in P-T dependence under SSP1–2.6 and SSP5–8.5 scenarios. New hydrological insight for the region: Observations show spatial diversity, with strong negative associations in central, western, and coastal regions, while positive associations are prominent in the Western Ghats and northeastern regions. CMIP6 models show mixed performance in capturing the spatial patterns and temporal evolution of P-T dependence. The EC-Earth model simulations effectively replicate the observed P-T dependence. In contrast, models such as ACCESS-ESM1–5, CanESM5, and ACCESS-CM2 exhibit discrepancies when compared to observations, suggesting that their future projections should be interpreted with caution. Projections under high-emission scenarios indicate a widespread increase in P-T dependence, particularly in northern and central areas, highlighting an increased likelihood of compound extremes.